Promiscuous Recognition of a Trypanosoma cruzi CD8+ T Cell Epitope among HLA-A2, HLA-A24 and HLA-A1 Supertypes in Chagasic Patients. - Paola Lasso; Lina Beltrán; Fanny Guzmán; Fernando Rosas; M Carmen Thomas; Manuel Carlos López; John Mario González; Adriana Cuéllar; Concepción J Puerta (PLoS ONE, 2016)
Background TcTLE is a nonamer peptide from Trypanosoma cruzi KMP-11 protein that is conserved among different parasite strains and that is presented by different HLA-A molecules from the A2 supertype. Because peptides presented by several major histocompatibility complex (MHC) supertypes are potential targets for immunotherapy, the aim of this study was to determine whether MHC molecules other than the A2 supertype present the TcTLE peptide. Methodology/principal findings From 36 HLA-A2-negative chagasic patients, the HLA-A genotypes of twenty-eight patients with CD8+ T cells that recognized the TcTLE peptide using tetramer (twenty) or functional (eight) assays, were determined. SSP-PCR was used to identify the A locus and the allelic variants. Flow cytometry was used to analyze the frequency of TcTLE-specific CD8+ T cells, and their functional activity (IFN-γ, TNFα, IL-2, perforin, granzyme and CD107a/b production) was induced by exposure to the TcTLE peptide. All patients tested had TcTLE-specific CD8+ T cells with frequencies ranging from 0.07-0.37%. Interestingly, seven of the twenty-eight patients had HLA-A homozygous alleles: A*24 (5 patients), A*23 (1 patient) and A*01 (1 patient), which belong to the A24 and A1 supertypes. In the remaining 21 patients with HLA-A heterozygous alleles, the most prominent alleles were A24 and A68. The most common allele sub-type was A*2402 (sixteen patients), which belongs to the A24 supertype, followed by A*6802 (six patients) from the A2 supertype. Additionally, the A*3002/A*3201 alleles from the A1 supertype were detected in one patient. All patients presented CD8+ T cells producing at least one cytokine after TcTLE peptide stimulation. Conclusion/significance These results show that TcTLE is a promiscuous peptide that is presented by the A24 and A1 supertypes, in addition to the A2 supertype, suggesting its potential as a target for immunotherapy.